PERANAN POLISI DALAM MENANGGULANGI TINDAK PIDANA PERJUDIAN (STUDI KASUS DI WILAYAH HUKUM POLSEK DELI TUA) - NANCI YOSEPIN SIMBOLON (JURNAL ILMIAH MAKSITEK, 2019)
Narcotics problem in Indonesia is still an urgent and complex problem. Within the last decade, the narcotics problem has become more prevalent. the network. Illicit drug trafficking has spread throughout the territory of the country of Indonesia ranging from big cities to small cities.The analysis used in this legal research is normative legal research which uses various secondary data such as statutory regulations, court decisions, legal theories, law books and the opinions of legal scholars relating to narcotics. This research was conducted based on legal principles and analyzed Decision Number 2564 / Pi d.Sus / 2017 / PN.Mdn regarding the case of Narcotics Class I distribution.This study aims to find out how the legal regulation of narcotic crime in Indonesia, to find out how the application of the law by the panel of judges against the conviction of narcotics offenders in Decision Number 2564 / Pid.Sus / 2017 / PN.Mdn, and to find out how legal considerations by panel of judges against the conviction of narcotics offenders in Decision Number 2564 / Pid.Sus / 2017 / PN.Mdn. The eradication of narcotics distribution must be prevented and dealt with firmly and readily by law enforcement officials. Where law enforcement as the main milestone in the eradication of narcotics crime must be active in making efforts to prevent and control narcotics distribution. The prevention of narcotics distribution in Indonesia should be carried out by actively involving the community, increasing the legal awareness of the community, and conducting counseling and socialization to the community, not only in big cities but up to small towns.